Perbandingan Lembaga Anti-Korupsi: Studi KPK Indonesia dan CPIB Singapura - Ragil Triokta Handayani; Anza Ronaza Bangun (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2026)
. Corruption is an extraordinary crime that has a systemic impact on economic stability, governance and the protection of human rights. Indonesia and Singapore show significant differences in the effectiveness of corruption eradication, despite both applying the rule of law principle. Indonesia established the Corruption Eradication Commission (KPK) through Law Number 30 of 2002 jo. Law No. 19/2019 as an independent institution with powers to investigate and prosecute, but its effectiveness has been weakened by political interference, regulatory revisions, and bureaucratic obstacles. Singapore, on the other hand, relies on the Corrupt Practices Investigation (CPIB) under the Prevention of Corruption Act 1960, which has historical legitimacy, stable political support, and consistent regulations. This difference in effectiveness is reflected in the 2024 Corruption Perception Index, where Indonesia ranks 99th with a score of 37/100, while Singapore ranks 3rd with a score of 84/100. Although the KPK normatively has broader authority, 2024, where Indonesia ranked 99th with a score of 37/100, while Singapore ranked 3rd with a score of 84/100. Although the KPK normatively has broader authority, empirical results show that the success of corruption eradication is determined by institutional integrity, regulatory consistency, and structural independence. This research uses a normative juridical method with a literature study approach and deductive thinking method to analyze the legal basis, and implementation of the two institutions. The results of this study found that the differences between the anti-corruption institutions of the two countries do not merely depend on legal instruments, but on political structure, organizational culture, and institutional commitment in upholding integrity. It is expected to provide normative recommendations to strengthen Indonesia's anti-corruption institution, namely the KPK, through structural, regulative, and institutional reforms